The Effectiveness of the Role of Provincial Covid-19 Task Force (Satgas) in Accelerating the Handling of Covid-19 in DKI Jakarta - Khikmatul Islah; Ivan Budi Susetyo; Zakia Zakia (Budapest International Research and Critics University, 2022)
DKI Jakarta as an area that is the center for the entry and exit of migrants from within and outside the country, and is the first transmission area to carry out various preventive measures for the Covid-19 pandemic. The DKI Jakarta Provincial Government reviewed and restricted crowd permits after the announcement of the first 2 positive Covid-19 patients. Various efforts have been made by the Governor of DKI Jakarta, Anies Baswedan, including launching the official Covid-19 website (corona.jakarta.go.id) and forming a special team that will be tasked with monitoring and supervising the potential spread of Covid-19, namely the DKI Covid-19 Response Team. Jakarta through Governor Decree No. 291/2020 regarding the Inauguration of the DKI Jakarta Covid-19 Response Team, which is then adjusted to the following: Presidential Decree No. 7/2020 concerning the Task Force (Satgas) for the Acceleration of Handling Corona Virus Disease 2019. Large-Scale Social Restrictions (PSBB) are a policy taken by the DKI Jakarta Provincial Government in an effort to handle the spread of the corona virus, because the number of cases due to the disease is increasing and spreading significantly and rapidly to several areas in DKI Jakarta. In the implementation, the Government of DKI Jakarta Province first applied PSBB on April 10, 2020 and extended continuously up to several times. Based on the development of the policy change from the application of PSBB to the Transitional PSBB and subsequently re-implementing the PSBB, this study will discuss the Effectiveness of the Role of provincial Covid-19 Task Force (Satgas) in Accelerating the Handling of Covid-19 in DKI Jakarta. In this research, the method used is starting with data collection through in-depth interviews and documentation studies. Then triangulation was carried out to validate the data before finally analyzing the data from the in-depth interviews and documentation studies. The result of this study indicate that the provincial covid-19 Task Force has played an effective role in accelerating the handling of the Covid-19 pandemic in DKI Jakarta.